For a general narratology of discourse (linguistic, visual, sonorous, audiovisual) non-indirect, indirect, no-direct and direct - Nadal, José María (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The article describes two basic operations of general narratology, which always accompany the narrative-thematic-figurative predication of inventio in a linguistic, visual, sonorous or audiovisual discourse: discursivation and appreciation. Based on them, he defines four basic types of discourse: non-direct and non-indirect, non-direct and indirect, direct and non-indirect, and direct and indirect. It addresses the relationship between appreciation and discursivation, and between direct and indirect speech. Finally, he relates the dialogism of Bakhtin, Volosinov and Ponzio with discursivation and appreciation; with the general scheme of the forms of expression and content; and with the functions of said forms in the semiotic intellectio, that is, with the interaction between the implicit enunciator and implicit enunciatee. All of this applies to an advertisement for Patrichs fragrance.